Effects of 8 weeks of high-intensity interval training or resistance training on muscle strength, muscle power and cardiorespiratory responses in trained young men - Molinari, T.; Molinari, T.; Rabello, R.; Rodrigues, R. (Sport Sciences for Health, 2022)
Purpose The aim of this study was to compare the effects of 8 weeks of resistance training (RT) and high-intensity interval training (HIIT) on muscle strength, muscle power and cardiorespiratory responses in trained young men.